Bathsheba [large type] : reluctant beauty - Hunt, Angela Elwell, 1957- (Hunt, Angela Elwell, 1957- Dangerous beauty novel., 2016)
Combining historical facts with detailed fiction, Angela Hunt paints an eye-opening portrait of the beautiful and misunderstood woman who struggled to survive the dire results of divine judgment on a king with a divided heart.